(e) [p, f(f)] (f) [â, Ħ] for general potential V (x)
Related questions
Question
Please answer (e) and (f)
![4. Calculate the following commutators
(Recall that [Â, B] = ÂB – BÂ= -[B, Â)
(a) [â, î]
(b) [â, î]
(c) [â²,p]
(d) [â, ƒ(â)]
(e) [p, f(â)]
(f) [î, H] for general potential V (x)](/v2/_next/image?url=https%3A%2F%2Fcontent.bartleby.com%2Fqna-images%2Fquestion%2F0d2fdd51-a813-4b36-89e9-f9581acfc2ee%2F583fc622-dda5-4727-a31e-2643220b3a12%2F20zp9c8_processed.jpeg&w=3840&q=75)
Transcribed Image Text:4. Calculate the following commutators
(Recall that [Â, B] = ÂB – BÂ= -[B, Â)
(a) [â, î]
(b) [â, î]
(c) [â²,p]
(d) [â, ƒ(â)]
(e) [p, f(â)]
(f) [î, H] for general potential V (x)
Expert Solution
![](/static/compass_v2/shared-icons/check-mark.png)
Step 1
[?,?(?)]?=(??(?)−?(?)?)?
knowing that ?=−?ℏ∂∂? you'll get
[?,?(?)]?=−?ℏ∂∂?(?(?)?)+?ℏ?(?)∂∂??=−?ℏ?∂∂??(?)−?ℏ?(?)∂∂??+?ℏ?(?)∂∂??
from where you find that [?,?(?)]=−?ℏ∂∂??(?)
Step by step
Solved in 2 steps with 1 images
![Blurred answer](/static/compass_v2/solution-images/blurred-answer.jpg)